We are the light - Quick, Matthew, 1973- (Avid Reader Press, 2022)
"Lucas Goodgame lives in Majestic, Pennsylvania, a quaint suburb that has been torn apart by a recent tragedy. Everyone in Majestic sees Lucas as a hero--everyone, that is, except Lucas himself. Insisting that his deceased wife, Darcy, visits him every night in the form of an angel, Lucas spends his time writing letters to his former Jungian analyst, Karl. It is only when Eli, an eighteen-year-old young man whom the community has ostracized, begins camping out in Lucas's backyard that an unlikely alliance takes shape and the two embark on a journey to heal their neighbors and, most importantly, themselves"--